Analisis Peran Sektor Pertanian Dalam Pengurangan Kemiskinan dan Peningkatan Kesejahteraan di Negara-Negara Berkembang - Diana Syahputri; Sofia Lubis; Bunga Anggraini (FEB Universitas Maritim Semarang, 2024)
This article examines the role of the agricultural sector in efforts to reduce poverty and enhance welfare in developing countries. The primary objective of this research is to analyze the extent to which the agricultural sector can contribute to the improvement of social and economic conditions in these nations. The research method involves the analysis of secondary data from various sources, including agricultural production data, food consumption patterns, and socio-economic and policy factors that influence the agricultural sector. The results of the study indicate that the agricultural sector plays a significant role in reducing poverty and enhancing welfare in developing countries. Firstly, the agricultural sector provides employment opportunities for a significant portion of the rural population, often the most vulnerable to poverty. Consequently, the agricultural sector contributes to increased income and access to economic resources for rural communities. Secondly, the agricultural sector also plays a crucial role in providing sufficient and affordable food for the population in developing countries. This positively impacts nutrition and public health, subsequently affecting the quality of life and overall welfare. By improving productivity and access to food resources, the agricultural sector can help reduce hunger and malnutrition. Thirdly, the agricultural sector has the potential to support national economic growth by supplying raw materials to the food processing and textile industries. This creates additional economic opportunities and enhances the competitiveness of developing countries in the global market.